UCDP Non-State Conflict Dataset - Sundberg, Ralph; Eck, Kristine; Kreutz, Joakim (Uppsala University, 2015)
The UCDP, Uppsala Conflict Data Program, contains information on a large number data on organised violence, armed violence, and peacemaking. There is information from 1946 up to today, and the datasets are updated continuously. The data can be downloaded for free.

The UCDP Non-Sate Conflict Dataset is a conflict-year dataset with information of communal and organized armed conflict where none of the parties is the government of a state. The dataset has a temporal scope covering 1989-2013, and includes information on start and end dates, fatality estimates, and locations.

The UCDP Non-State conflict project has been developed with support from the Human Security Report Project, Simon Fraser University, in Vancouver,Canada.

Purpose:

The Uppsala Conflict Data Program (UCDP) collects information on a large number of aspects of armed violence since 1946.

Cite as:
Sundberg, Ralph, Kristine Eck and Joakim Kreutz, 2012, "Introducing the UCDP Non-State Conflict Dataset", Journal of Peace Research, March 2012, 49:351-362

UCDP, Uppsala Conflict Data Program vid Uppsala universitet, innehåller stora mängder data över organiserat våld, väpnade konflikter och fredsarbete. Idag täcker UCDP´s data över hela världen, från 1946 och framåt, och finns presenterade i 13 olika dataset som kontinuerligt uppdateras. Datan finns tillgänglig för gratis nedladdning och användning via UCDP´s hemsida.

UCDP Non-State Conflict Dataset, baserat på konflikt-år, innehåller information om väpnade konflikter där ingen av parterna är regering i något land. Datasetet täcker tidsperioden 1989-2013 och innehåller bland annat information om start- och slutdatum för konflikten, uppskattning av antal dödade och konfliktens geografiska lokalisering.

Syfte:

Syftet för UCDP är att samla olika typer av information om väpnade konflikter från hela världen, från 1946 fram till idag.

Citera som:
Sundberg, Ralph, Kristine Eck and Joakim Kreutz, 2012, "Introducing the UCDP Non-State Conflict Dataset", Journal of Peace Research, March 2012, 49:351-362
UCDP Non-State Conflict Dataset
Keywords: international conflict; internationella konflikter; internal political conflict; inrikespolitiska konflikter; conflict; konflikt; war; krig; civil war; inbördeskrig; armed forces; väpnade styrkor; war deaths; dödade i krig; Conflict, security and peace; Konflikter, säkerhet och fred; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap